1997
DOI: 10.1017/s0954579497001478
|View full text |Cite
|
Sign up to set email alerts
|

Development and the fragmented self: Longitudinal study of dissociative symptomatology in a nonclinical sample

Abstract: Dissociative behaviors and their relation to both the self and self-organization were examined using the developmental psychopathology perspective in a prospective longitudinal study of high-risk children. Participants were 168 young adults (n = 79 females, n = 89 males, age = 18–19 years) considered high-risk for poor developmental outcomes at birth due to poverty. The present study investigated whether trauma, sense of self, quality of early mother–child relationship, temperament, and intelligence were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
349
3
27

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(406 citation statements)
references
References 7 publications
(17 reference statements)
27
349
3
27
Order By: Relevance
“…16,[44][45][46][47][48][49] It has been suggested that the development of dissociation, reflecting severe deficits in the integration of the self, can be an outcome of CM, 50 and severity and chronicity of maltreatment have been found to predict future levels of dissociation. 51 In particular, a meta-analysis, evaluating 26 studies with 2108 subjects involved, reports a positive association between CM and dissociation regardless of the type of abuse. 52 On the other hand, the association between Abbreviation: SRS, sex reassignment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16,[44][45][46][47][48][49] It has been suggested that the development of dissociation, reflecting severe deficits in the integration of the self, can be an outcome of CM, 50 and severity and chronicity of maltreatment have been found to predict future levels of dissociation. 51 In particular, a meta-analysis, evaluating 26 studies with 2108 subjects involved, reports a positive association between CM and dissociation regardless of the type of abuse. 52 On the other hand, the association between Abbreviation: SRS, sex reassignment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Subscale 2 was developed by Ogawa et al (1997) to assess dissociation using twelve items from the CBCL and the CBCL Teacher Report Form. The authors chose items that corresponded to the CDC, excluding those items related to inappropriate sexual behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Ogawa, Sroufe, Weinfeld, Carlson, and Egeland (1997) also examined the impact of maltreatment on dissociation over time. Using prospective, longitudinal data from a sample of at-risk children, they found that maltreatment predicted dissociation at all developmental stages, from toddlerhood to adulthood.…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors routinely refer to the "dissociative defense," and to "dissociative coping" responses, or begin their articles with phrases like "it is widely accepted that" or "most theorists agree that" dissociative states are "ways of coping with exceptional situations," or serve "a defensive function against situations of stress" (Collins and French 1998;Terr 1991;Silon 1992;Foa and Hearst-Ikeda 1996;Nijenhuis et al 1998;Ogawa et al 1997;Briere 2006;Briere et al 2005;Simoneti et al 2000;Goodwin and Sachs 1996;Martinez-Taboas and Bernal 2000). Thus, in more recent work, the paradigm is widespread and structures researchers' approaches to dissociation without itself being the topic of empirical research.…”
Section: The Psychiatric-adaptive Paradigmmentioning
confidence: 99%